THE INFLUENCE OF PHYSICAL METHODS OF VEGETABLES PROCESSING ON THE QUALITY OF FROZEN PRODUCTS - N. S. Shishkina; O. V. Karastoyanova; L. A. Borchenkova; N. V. Korovkina; N. I. Fedyanina (Пищевые системы, 2019)
The indicators of quality and microbiological safety of frozen vegetable semi-finished products (for example, cut beet) processed in a microwave field for subsequent storage for 18 months at a temperature of minus 20±2 °C. Treatment with a microwave field was carried out under the following conditions: power 600 W and duration 5 min (180 kJ); power 1000 W and duration 4 min (240 kJ). It is established that treatment in the microwave field contributes to the preservation of consumer qualities of the product (total solids content, mass fraction of soluble solids, bound moisture content, microbiological effect) in the process of long-term low-temperature storage.